Osteomyelitis in a Paediatric Patient with Sub-periosteal Abscess, Septic Pulmonary Emboli and Pneumothorax: A Case Report - Tamang, Ongden Yonjen; Maharjan, Santosh; Upadhyaya, Rudra Prasad; Shrestha, Ashish (Nepalese Journal of Radiology, 2024)
Osteomyelitis is an inflammatory disorder affecting bone and adjacent tissue that primarily arises from pyogenic bacteria, often involving the metaphysis of long bones in pediatric patients through hematogenous spread with the common pathogen being Staphylococcus aureus. Complications such as pathological fractures, sinus formation, and abscesses, may occur. Septic pulmonary embolism (SPE), a rare complication, can lead to infarctions and abscesses in pulmonary vessels. Pneumothorax secondary to SPE can also occur, emphasizing the importance of considering these complications in patients with features of sepsis.